2019
DOI: 10.1101/575662
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chestnut extract but not sodium salicylate decrease the severity of diarrhea and enterotoxigenic Escherichia coli F4 shedding in artificially infected piglets

Abstract: 19The development of alternatives to antibiotics is crucial to limiting the incidence of antimicrobial 20 resistance, especially in prophylactic and metaphylactic use to control post-weaning diarrhea 21 (PWD). Feed additives, including bioactive compounds, could be a promising alternative. This 22 study aimed to test two bioactive compounds, sodium salicylate (SA) and a chestnut extract 23 (CE) containing hydrolysable tannins, on the occurrence of PWD. At weaning, 72 piglets were 24 assigned to four treatments… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In fact, the combined effect of Ch/Qu tannins could be exacerbated during stressful conditions, such as experimental bacterial infections [ 24 , 28 ]. According to Reggi et al [ 16 ], beneficial effects were reported when Ch/Qu digesta were administered to experimentally stressed intestinal swine cells, suggesting that it might have a trophic effect at the intestinal epithelium, and an increased viability of cells was observed after tannin treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the combined effect of Ch/Qu tannins could be exacerbated during stressful conditions, such as experimental bacterial infections [ 24 , 28 ]. According to Reggi et al [ 16 ], beneficial effects were reported when Ch/Qu digesta were administered to experimentally stressed intestinal swine cells, suggesting that it might have a trophic effect at the intestinal epithelium, and an increased viability of cells was observed after tannin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneous results were obtained on the effects of Ch and Qu to enhance growth performance, modulate intestinal microbiota, and decrease the incidence of diarrhea during the post-weaning period [ 22 , 23 , 24 ]. These heterogeneous results could be related to the chemical characteristics of tannins, which can compromise the palatability, digestibility, and protein use of feed.…”
Section: Introductionmentioning
confidence: 99%
“…and quebracho (Qu, Schinopsis spp.) tannin extracts have been used for over ten years in animal feeding [4][5][6]. Although tannins can interfere with the digestion of nutrients as they bind proteins and delay the absorption of sugar and lipids, several studies have reported that the addition of Qu and Ch to animal feed improved the growth performance and health in both ruminants and monogastric animals [4,5,7].…”
Section: Introductionmentioning
confidence: 99%